2020
DOI: 10.7861/clinmed.2020-0424
|View full text |Cite
|
Sign up to set email alerts
|

C-reactive protein and albumin association with mortality of hospitalised SARS-CoV-2 patients: A tertiary hospital experience

Abstract: The objective was to study hospitalised COVID-19 patients' mortality and intensive care unit (ICU) admission with covariates of interest (age, gender, ethnicity, clinical presentation, comorbidities and admission laboratory findings). Methods Logistic regression analyses were performed for patients admitted to University Hospital, University Hospitals Coventry and Warwickshire NHS Trust, between 24 January 2020-13 April 2020. Results There were 321 patients hospitalised. Median age was 73 years and 189 (59%) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
28
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 23 publications
(30 reference statements)
5
28
0
2
Order By: Relevance
“…Hypoalbuminemia followed by massive fluid loss due to severe infection is also responsible for hypovolemia and shock in these patients [23]. Correlation of albumin levels and severity of the infection is presented through the specific CRP/albumin ratio, already marked as an independent risk factor for severe COVID-19 infection [24,25]. IL-6 induces oxidative stress and endothelial dysfunction by overexpression of the Angiotensin II type 1 receptor, which was presented 15 years ago in paperwork by Wassman et al [26].…”
Section: Discussionmentioning
confidence: 99%
“…Hypoalbuminemia followed by massive fluid loss due to severe infection is also responsible for hypovolemia and shock in these patients [23]. Correlation of albumin levels and severity of the infection is presented through the specific CRP/albumin ratio, already marked as an independent risk factor for severe COVID-19 infection [24,25]. IL-6 induces oxidative stress and endothelial dysfunction by overexpression of the Angiotensin II type 1 receptor, which was presented 15 years ago in paperwork by Wassman et al [26].…”
Section: Discussionmentioning
confidence: 99%
“…Kawasaki disease and acute respiratory distress syndrome are of concern to clinicians, and inclusion of CAR in the initial evaluation of hospital admissions may make it possible to identify and closely monitor patients in whom these conditions may develop. In addition, although there are currently no standardized criteria for COVID-19 patients to be admitted to intensive care units [31] , it may be possible to classify patients requiring strict monitoring and early possible therapeutic intervention by using CAR as a risk factor.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike our results which showed paraclinical and biochemical data have limited predictive value, in the model developed by Zhao et al (AUC 0.83), lactate dehydrogenase and procalcitonin were among the top mortality prediction factors [ 20 ], and the COVID-AID study showed that renal failure at presentation (defined by creatinine > 2 mg/dL), regardless of chronicity has a high impact on in-hospital mortality in hospitalized COVID-19 patients [ 21 ]. Recent studies have reported that prothrombin and CRP are associated with COIVD severity and mortality [ 22 , 23 ]. In this study, we showed the correlation of decreased O2 and increased lactate that may indicate the higher level of the anaerobic metabolism [ 24 ] in patients with COVID-19 that are associated with mortality.…”
Section: Discussionmentioning
confidence: 99%